COMPARISON OF RICERCA INDEX VALUES AS A SCREENING METHOD FOR BETA THALASSEMIA MINOR AND IRON DEFICIENCY ANEMIA AT PROF. DR. MARGONO SOEKARJO HOSPITAL - Talitha Daffa Amadea; Agus Fitrianto; Tri Lestari (Mandala Of Health, 2026)
Beta thalassemia minor and iron deficiency anemia (IDA) are the most common causes of microcytic hypochromic anemia with similar laboratory features but require different management approaches, making differentiation between these two conditions often challenging. The Ricerca index is a simple screening method based on RDW and RBC parameters that can distinguish beta thalassemia minor from IDA. To analyze the optimal cut-off, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of the Ricerca index in differentiating beta thalassemia minor from iron deficiency anemia at Prof. Dr. Margono Soekarjo Regional General Hospital. This was an analytical observational study with cross-sectional design using consecutive sampling from secondary data of medical records of patients aged ≤18 years during the 2020-2025 period, obtaining 40 subjects with beta thalassemia minor and 40 subjects with IDA. The Ricerca index value was calculated using the RDW/RBC formula. Diagnostic test analysis of the Ricerca index was performed using Receiver Operating Characteristic (ROC) curve. There were significant differences in the distribution of subject age, Hb and RBC values, and Ricerca index values between both groups (ρ<0.001). The optimal cut-off value of the Ricerca index was <4.3 for beta thalassemia minor and >4.3 for IDA. The Area Under the Curve (AUC) value was 0.861 (95% CI: 0.776-0.945; ρ<0.001). The sensitivity, specificity, PPV, and NPV of the Ricerca index for beta thalassemia minor were 77.50%, 80.00%, 79.49%, and 78.05%, respectively, while for IDA they were 80.00%, 77.50%, 78.05%, and 79.49%, with a Youden index of 0.58. The Ricerca index has good diagnostic performance with an accuracy of 86.1%, making it suitable for use as a screening method to differentiate beta thalassemia minor from IDA.